Should a hospitalized child receive empiric treatment with acyclovir? - Kulik Dina M; Mekky Magda; Yang Ming; Bitnun Ari; Parkin Patricia C (BMC, 2012)
Abstract Background Herpes simplex encephalitis is associated with substantial morbidity and mortality and may be related to timely diagnosis and treatment. While awaiting the results of testing, hospitalization and empiric treatment with acyclovir is recommended, though the direct and indirect costs associated with this management are substantial. We sought to examine children hospitalized for possible herpes simplex encephalitis, following clinical and laboratory assessment in the emergency department, and empiric treatment with acyclovir, in order to describe the proportion receiving a complete course of treatment; and to identify the clinical variables which are associated with receiving a complete course, as compared with an incomplete course of acyclovir. Methods Hospitalized children prescribed acyclovir were included in this case control study. Clinical, laboratory and diagnostic variables were abstracted for children prescribed a complete (≥ 14 days) or an incomplete course (<14 days) of acyclovir. Odds ratios and 95% confidence intervals were calculated. Results 289 children met eligibility criteria, 30 (10%) received a complete course and 259 (90%) received an incomplete course. A history of mucocutaneous herpes simplex virus infection (p < 0.01), Glasgow Coma Scale ≤ 13 (p = 0.02), focal neurologic findings (p = 0.001) and elevated cerebrospinal fluid white blood cell count (p = 0.05) were associated with a complete course of acyclovir. Conclusions Many children did not complete a full course of therapy. Unnecessary testing and treatment is burdensome to families and the health care system. Possible predictive variables include abnormal Glascow Coma Scale, focal neurologic findings and cerebrospinal fluid pleocytosis.